Association between HOMA-IR and ovarian sensitivity index in women with PCOS undergoing ART: A retrospective cohort study - Li, Yan; Wang, Yiwen; Liu, Hai; Zhang, Shaodi; Zhang, Cuilian (Frontiers in Endocrinology, 2023)
Insulin resistance (IR) may play a central role in the pathophysiology of polycystic ovary syndrome (PCOS). Controlled ovarian stimulation (COS) in PCOS women in the setting of assisted reproductive technology (ART) is always a challenge for clinicians. However, it remains unclear whether IR in women with PCOS correlates with reduced ovarian sensitivity to exogenous gonadotropin (Gn). This study aimed to explore the association between homeostasis model assessment of insulin resistance (HOMA-IR) and ovarian sensitivity index (OSI). In this retrospective cohort study, 1508 women with PCOS (Rotterdam criteria) aged 20-39 years undergoing their first oocyte retrieval cycle were included consecutively between 2018 until 2022. After confirming that there was a negative relation between Ln HOMA-IR and Ln OSI based on smoothing splines generated by generalized additive model (GAM), the association of HOMA-IR with OSI was further tested with a multivariable linear regression model and subgroup analysis. Our study provided evidence for the inverse correlation between IR and the ovarian sensitivity during COS. Herein, we proposed new insights for individualized manipulation in PCOS patients with IR undergoing ART.